Hidden actions and preferences for timing of resolution of uncertainty - Todd Sarver; Haluk Ergin (Theoretical Economics, 2015)
We study preferences for timing of resolution of objective uncertainty in a menu-choice model with two stages of information arrival. We characterize a general class of utility representations called hidden action representations, which interpret an intrinsic preference for timing of resolution of uncertainty as if an unobservable action is taken between the resolution of the two periods of information arrival. These representations permit a richer class of preferences for timing than was possible in the model of Kreps and Porteus (1978) by incorporating a preference for flexibility. Our model contains several special cases where this hidden action can be given a novel economic interpretation.
Keywords: D81; 330; Temporal preferences; preference for flexibility; hidden action; subjective uncertainty